Indonesian Millennial Customer Satisfaction Analysis in Online to Offline (O2O) Shopping: The Influence of O2O Shift and Service Quality on Customer Purchase Decisions - Andriyanto, Wahyu Ari; Suhardiyah, Martha; Pudji Estiasih, Soffia; Ria Jessika, Yati; Widhayani, Puri Setioningtyas (Universitas Brawijaya, Indonesia, 2025)
The urgency of this study is driven by the rapid development of online to offline (O2O) shopping platforms, which millennial consumers increasingly use in Indonesia. The shift from online to offline shopping and the quality of service provided are believed to significantly impact consumer purchase decisions. This study aims to analyze how the O2O shift and service quality influence the purchase decisions of millennial consumers in Indonesia. The method used in this study is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS application to analyze data obtained from 100 respondents selected using purposive sampling. The results of the analysis show that the online and offline shifts positively and significantly impact service quality. Furthermore, the O2O shift also positively and significantly influences customer purchase decisions. Service quality, in turn, was found to have a positive and significant effect on purchase decisions. These findings emphasize the importance of integrating both online and offline shopping experiences to enhance service quality and influence purchase decisions among millennial customers in Indonesia. This study contributes to understanding how O2O strategies can be leveraged to improve customer satisfaction and drive purchasing behavior. The novelty of this study lies in its approach, which integrates the effects of the O2O transition and service quality simultaneously, a perspective not extensively explored in previous studies related to millennial consumers in Indonesia. Practical implications of this study suggest that companies need to consider seamless integration between online and offline platforms to enhance customer experiences and drive purchase decisions.